2006
DOI: 10.1016/j.margeo.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Vertical grain-size variability within a turbidite levee: Autocyclicity or allocyclicity? A case study from the Rhône neofan, Gulf of Lions, Western Mediterranean

Abstract: The fining upward trend commonly described on levees of turbidite systems can be either attributed to changes in the sediment supply (external forcing = allocyclic) or changes in the spillover processes related to the growth of the levee (internal forcing = autocyclic). However the real causes remain speculative and difficult to demonstrate. Knowledge of vertical change in flow velocity (or grain size) in turbidity currents, of the turbidity current's height, as well as the growth rate of a levee are theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 42 publications
0
47
1
Order By: Relevance
“…Coarse-grained and silt-sand deposits have already been reported in the study area (Méar and Gensous, 1993;Beaudouin et al, 2004;Bonnel et al, 2005;Dennielou et al, 2006) and interpreted as originating from the PRC and its prolongation as a turbiditic channel. Dispersal of spillover flows from the turbiditic neochannel is believed to be the main pathway until it ended around 15 000 14 C yr BP (low stand and initial stages of post-glacial) (Bonnel et al, 2005;Dennielou et al, 2006).…”
Section: Source Of Turbidite Bedsmentioning
confidence: 58%
See 3 more Smart Citations
“…Coarse-grained and silt-sand deposits have already been reported in the study area (Méar and Gensous, 1993;Beaudouin et al, 2004;Bonnel et al, 2005;Dennielou et al, 2006) and interpreted as originating from the PRC and its prolongation as a turbiditic channel. Dispersal of spillover flows from the turbiditic neochannel is believed to be the main pathway until it ended around 15 000 14 C yr BP (low stand and initial stages of post-glacial) (Bonnel et al, 2005;Dennielou et al, 2006).…”
Section: Source Of Turbidite Bedsmentioning
confidence: 58%
“…Open circles indicate sediment cores. from the neochannel have stopped (Beaudouin et al, 2004;Bonnel et al, 2005;Dennielou et al, 2006). 12 kHz (EM12) and 30 kHz (EM300) multi-beam backscatter data, from previous studies (Droz, 1983;Bonnel et al, 2005) revealed two lobe-shaped adjacent areas at the outlet of the Sète canyon network and at the outlet of the La Fonera Canyon (LFC), with respectively heterogeneous low backscatter and lineated moderate backscatter (Droz et al, 2001;Bonnel et al, 2005) (Fig.…”
Section: Morpho-sedimentary Settingmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the sands are only deposited by flows that are suspending sand grains higher than the active levee crest, whereas muds are suspended above the levee crest during nearly every flow. Therefore, sandstone bed thickness is indicative of a single flow event, whereas the mud event bed boundaries are likely indistinguishable (Dennielou et al, 2006), producing higher characteristic mudstone bed thickness. The higher mudstone-thinning rate is due to the high degree of thin bedded sandstone beds lumping into a single mud bed, inability for complete sandstone correlation, and indistinguishable mudstone bed boundaries within the original panel creating a rapid mudstone bed thickness change and increased thinning rate.…”
Section: Lateral Event Bed Continuity Between Depositional Environmenmentioning
confidence: 99%